HIV/AIDS needs and concerns of immigrant Latinas in San Miguel County: an exploratory study - Gonzales Garcia, Karla Giovanna, author; Vernon, Irene, advisor; Souza, Caridad, committee member; Griffin, Cindy, committee member (Colorado State University. Libraries, 2016)
Working on creating paths to end gender, class and racial health inequalities in the U.S, this qualitative study explores the perspectives of immigrant Latinas on knowledge, cultural understandings, and access and barriers to HIV/AIDS services in San Miguel County, CO. Following a community based participatory research process through the use of intersectional lenses and transnational multiracial feminism, this research process seeks to further augment the literature on prevention intervention on HIV/AIDS, as well as to contribute to the construction of policies and recommendations based on their lived experiences. Grounded theory was used for data analysis to maintain women’s voices as the center of the research, where theory was constructed continuously based in their lived experiences and realities. Within this study, the interlocking relationship found between neoliberalism, transnationalism, U.S health care system and legal status, and the major themes such as, barriers to health care, HIV/AIDS related stigma and discrimination, Machismo, Latina sexuality, and knowledge of community resources, provides the context in which the epidemic of HIV/AIDS operates among immigrant Latinas.